Master of Science in Climate-Smart Agriculture Curriculum - Mwamburi, Mcharo; Kambura, Ann; Gacheru, James; Maghenda, Marianne; Jalang'o, Dorcas; Waswa, Boaz Shaban; Kinyua, Ivy Wambui; Templer, Noel; Mwongera, Caroline (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Food production faces interlinked challenges with increasing uncertainties from the increasing impacts of climate change and variability. The underlying philosophy of CSA is the development and promotion of an integrative approach that results in landscape management for productive croplands, livestock, forests, and fisheries. It aims for improved food and nutrition security and equitable livelihoods. The program seeks to support the achievement of three outcomes i.e. increased productivity (producing more food to improve food, nutrition, and income security and livelihood of the world’s resource-poor farmers in rural areas); enhanced resilience (contributing to training for reduced vulnerability to drought, pests, disease, and other shocks); reduced emissions (reducing emissions from production systems to protect the environment while increasing productivity); and improved capacity to adapt (increasing productivity in the face of extreme climatic weather patterns). The program anchors on existing knowledge, technologies, and principles of sustainable agriculture. The need to increase carbon sinks and reduce GHGs emissions is a priority consideration, especially during training for a sustainable agro-ecosystem. Its design explicitly focuses on addressing productivity and climate change mitigation and adaptation with consideration of the interactions and tradeoffs existing between them. Finally, the CSA program aims to support funding opportunities for innovation and technology development for extension through research investment.